The effect of strontium carbonate on cross-linking of pectin based free - Abrishami Kafi, Aida; Mehrabi, Adele; Akhgari, Abbas (International Pharmacy Acta, 2018)
Introduction: : Recently, considerable attention has been devoted to biopolymers because of their unique properties and high usage in different fields such as pharmaceutical industry, health promotion and cosmetic applications .Pectin is a high-molecular weight and anionic natural heteropolysaccharide extracted from cell walls of higher plants which is non-toxic and biocompatible.(1) A cross-link is a bond that links one polymer chain to another. Strontium (Sr+2) establish covalent bonds (chemical method) and physical interaction (physical method) between anionic pectin chains that makes polymer stronger. Methods and Results: : Firstly, specific amounts of pectin were dissolved in distilled water. Then, a fixed amount of triethyl citrate (1:6 ratio related to total polymer content) was added to solution as a plasticizer. After 24 hour, free film was cross-linked with 1% strontium carbonate solution for 1 minute .For swelling experiment, a piece of dried cross-linked and non cross-linked pectin based free film was weighted and immersed in flasks of dissolution test containing 250 ml of acidic media(PH=1.2) and phosphate buffer media(PH=6.8) at 37 ℃. sampling time was started from 2 minutes to 60 minutes. To quantify the swelling process, the swelling index, Is (%),was calculated(2). Thickness of both cross-linked and non cross linked pectin based free film was 0.16